2010
DOI: 10.4038/tare.v12i1.1984
|View full text |Cite
|
Sign up to set email alerts
|

Folk Media Preferences and Prospects for Agricultural Extension Service Delivery in Benue State, Nigeria

Abstract: The study investigated folk media preferences and prospect for use in agricultural extension service delivery in two Local Government Areas (LGAs) of Benue State. A total of 100 farmer respondents were selected using a random sampling technique. Data collected were analyzed using frequency, mean, percentage and chi-square. Majority (62%) of the respondents were married while 65% were males indicating a non gender sensitive population. A chi-square analysis of the degree of association between respondents' pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Hoivik and Lugar (2009) state that the effectiveness of folk media as part of rural social environment is that they are credible sources of information to local people. Daudu and Anyanwu (2009) in their study in Benue State, Nigeria, found that one of the major reasons for folk media usage in rural development is their effectiveness for information dissemination, entertainment and promotion of culture. Therefore, for the dominantly oral culture such as in the eastern Tigray, the effectiveness of folk media forms to convey food security messages is that they are an integral part of people's culture.…”
Section: Potential Of Folk Media Forms For Food Security Communicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Hoivik and Lugar (2009) state that the effectiveness of folk media as part of rural social environment is that they are credible sources of information to local people. Daudu and Anyanwu (2009) in their study in Benue State, Nigeria, found that one of the major reasons for folk media usage in rural development is their effectiveness for information dissemination, entertainment and promotion of culture. Therefore, for the dominantly oral culture such as in the eastern Tigray, the effectiveness of folk media forms to convey food security messages is that they are an integral part of people's culture.…”
Section: Potential Of Folk Media Forms For Food Security Communicationmentioning
confidence: 99%
“…The widespread acceptance and repeated use of these communication forms among rural people helps them to obtain a better knowledge and understanding of issues affecting them. Studies have shown that folk media forms possess various qualities to integrate them into rural development programs (Awa, 2005;Ugboajah, 1985;Salawu, 2015;Daudu & Anyanwu, 2009;Nigussie et al, 2010;Hoivik & Lugar, 2009). One of the qualities of folk media forms for rural development communication is that these communication forms are endogenous and are supported by the idioms and worldviews of local people.…”
Section: The Use Of Folk Media Forms For Development Communicationmentioning
confidence: 99%
See 2 more Smart Citations